(untitled) (Actual Problems of Psychology in Educational Institutions, 2020)
Abstract. The article discusses the essence and quality of modern educational space as a factor in the formation of the New Ukrainian School. Psychological and pedagogical trends and conditions for optimizing the educational process are analyzed in accordance with the tasks defined by the State standard of primary education. The importance of organizing an optimal classroom in the classroom according to the laws of ergonomics and aesthetics is disclosed. The urgency of observing the principle of continuity of preschool and primary education is noted. The author emphasizes that the competency-based approach to learning is an important resource for the personal development of a child. The conclusion is drawn about the need for systemic reform of primary education in the dimensions of the NUS.